EMPLOYMENT EFFECT OF INDONESIA’S NON-OIL EXPORT - Nur Feriyanto (Economic Journal of Emerging Markets, 2010)
Indonesian government needs both domestic and foreign investments to accelerate its economic development. The investments enable promoting export and creating higher employment level. This research uses a path analysis method to analyze time series data of the period 1990 to 2009. It finds that both domestic and foreign direct investments significantly and positively influence Indonesia’s non-oil exports. In addition, it suggests that non-oil export performance can eventually lead to an increase in employment level in Indonesia. The policy implication of these results is that Indonesian government should encourage investment to promote export and absorb more labor. Keywords: Foreign direct investment, domestic investment, non-oil export, labor absorptionJEL classification numbers: F42, F43